The Keroncong Song Jembatan Suramadu by Orkes Keroncong Kurmunadi: A Study of Arrangement and Characteristics - Kholifatul Amalia - (Universitas Negeri Surabaya, 2026)
This study aims to analyze the arrangement and describe the musical characteristics of the Keroncong Jembatan Suramadu song composed by Orkes Keroncong Kurmunadi, which reflects the group's musical identity. The method used is qualitative descriptive, with data collection techniques through observation, interviews, and documentation. Data analysis was conducted through reduction, presentation, and conclusion drawing. The results of the study show that this song has a complex structure (prelude, intro, phrases A, B, C, interlude, ole-ole, coda) with a distinctive repetition pattern. The song uses the key of G major, 4/4 time, Allegretto tempo, and I–IV–V–I chord progression. The arrangement combines varied melodic techniques, improvisation, and rich harmonies, along with a blend of classic keroncong style and modern elements. Instruments such as the cak, cuk, cello, violin, flute, and keyboard create harmonious colors and expressive dynamics. Overall, this song strongly and distinctively represents the musical character of the Kurmunadi Keroncong Orchestra.